THE ELEVENTH GRADE STUDENTS' READING HABITS IN ENGLISH - Aprilia, Nanda (Universitas Negeri Malang, 2024)
Since books are a repository of knowledge, reading habits aid students in being more prepared for a wider range of aspects in life. However, among Indonesian students studying English as a foreign language (EFL), the belief that reading is merely a hobby is still prevalent. Since reading is not their pastime, this provides a justification for people who don't want to read. This study was intended to investigate English reading habits of EFL students. A follow-up interview guide and a questionnaire were used in a mixed-method approach. The questionnaire was given out to 203 eleventh graders at SMAN 1 Purwosari, Pasuruan, East Java, Indonesia. The results demonstrated that the majority of eleventh grade EFL students did not exhibit proficient English reading habits. Despite, most of the students considered reading in English was a useful and enjoyable pastime that they typically engaged in during their spare time. Additionally, they listed a number of issues, the primary one being that they had not been exposed to reading English-language literature at an early age and that was why they preferred to read in their own tongue. This study has highlighted the necessity for educators and parents to create a calm and pleasant reading space for their children in order to foster positive English reading habits.